Natural Convection Heat Transfer in a Porous Cavity with Sinusoidal Temperature Distribution Using Cu/Water Nanofluid: Double MRT Lattice Boltzmann Method (Communications in Computational Physics, 2020)
In this study, natural convection flow in a porous cavity with sinusoidaltemperature distribution has been analyzed by a new double multi relaxation time(MRT) Lattice Boltzmann method (LBM). We consider a copper/water nanofluid filling a porous cavity. For simulating the temperature and flow fields, D2Q5 and D2Q9lattices are utilized respectively, and the effects of different Darcy numbers (Da) (0.001-0.1) and various Rayleigh numbers (Ra) ($10^3$-$10^5$) for porosity ($ε$) between 0.4 and 0.9have been considered. Phase deviation ($θ$) changed from 0 to $π$ and the volume fractionof nanoparticles (Ø) varied from 0 to 6%. The present results show a good agreementwith the previous works, thus confirming the reliability the new numerical methodproposed in this paper. It is indicated that the heat transfer rate increases at increasingDarcy number, porosity, Rayleigh number, the volume fraction of nanoparticles andphase deviation. However, the most sensitive parameter is the Rayleigh number. Themaximum Nusselt deviation is 10%, 32% and 33% for Ra=$10^3$, $10^4$ and $10^5$, respectively, with $ε = 0.4$ to $ε = 0.9$. It can be concluded that the effect of Darcy number onthe heat transfer rate increases at increasing Rayleigh number, yielding a maximumenhancement of the average Nusselt number around 12% and 61% for Ra=$10^3$ andRa=$10^5$, respectively.
Keywords: Porous media; double multi relaxation time-lattice Boltzmann method; nanofluid; natural convection; sinusoidal temperature distribution.